Christ and the created order: perspectives from theology, philosophy, and science - Torrance, Andrew; McCall, Thomas H. (Zondervan, 2018)
Theological perspectives. Jesus Christ, the order of creation / Murray Rae ; Creation through Christ / Norman Wirzba ; Jesus Christ the divine animal? The human distinctive reconsidered / Brian Brock ; Christ, creation and the powers: Elements in a Christian doctrine of creation / Brian Curry -- Biblical and historical perspectives. Christ and the cosmos: Kingdom and creation in gospel perspective / N.T. Wright ; Gospel narratives and the psychology of eyewitness memory / Richard Bauckham ; In him and through him from the foundation of the world: Adoption and christocentric anthropology / Erin M. Heim ; Paul, Christ, and narrative time / Chris Tilling -- Philosophical perspectives. For better for worse solidarity / Marilyn McCord Adams ; Our Chalcedonian moment: Christological imagination for scientific challenges / James K.A. Smith ; Convictional knowledge, science, and the spirit of Christ / Paul K. Moser ; Explaining the created order: Scientific and personal images / J.B. Stump -- Scientific perspectives. Christ and the cosmos: Christian perspectives on astronomical discoveries / Deborah Haarsma and Loren Haarsma ; Cognitive science, sensus divinitatis, and Christ / Tyler S. Greenway and Justin L. Barrett ; Science as the foolishness of God: twenty-eight theses and scholia on science and religion / Wilson Poon ; The scientist-believer: Following Christ as we uncover the wonders of the living world / Ruth M. Bancewicz